- #1

- 158

- 0

[tex]F(z) = \overline{f(\bar{z})}[/tex]

Thanks for the help.

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter fauboca
- Start date

- #1

- 158

- 0

[tex]F(z) = \overline{f(\bar{z})}[/tex]

Thanks for the help.

- #2

I like Serena

Homework Helper

- 6,579

- 176

The overbar notation indicates the complex conjugate.

Apparently the function F(z) is defined by taking the complex conjugate of z, applying the function f, followed by taking the conjugate of the result.

Note that for regular functions F(z) is equal to f(z).

- #3

- 158

- 0

The overbar notation indicates the complex conjugate.

Apparently the function F(z) is defined by taking the complex conjugate of z, applying the function f, followed by taking the conjugate of the result.

Note that for regular functions F(z) is equal to f(z).

I was hoping with this information I would have been able to solve the problem, but I am still unsure on how to work it.

The question is:

If [itex]f:\mathbb{C}\to\mathbb{C}[/itex] is entire, i.e. holomorphic at every point, then [itex]F(z) = \overline{f(\bar{z})}[/itex].

I am not sure how to do this problem. So we know f is differentiable everywhere. How does this help?

- #4

- 761

- 13

[tex] f(z) = \overline{f({\overline{z}}) }, [/tex]

if you write out f in a real and imaginary part and apply the CR conditions you'll find this quick and easy.

- #5

- 158

- 0

You'll need to prove that:

[tex] f(z) = \overline{f({\overline{z}})}, [/tex]

if you write out f in a real and imaginary part and apply the CR conditions you'll find this quick and easy.

I understand what you are saying but I still don't quite see it.

So if we let [itex]u(x,y)[/itex] be the real and [itex]v(x,y)[/itex] be the imaginary parts of F. How do I define them for [itex]\overline{f({\overline{z}})}[/itex]

- #6

- 761

- 13

[tex] f(z) = f(x,y) = u(x,y) + iv(x,y) \rightarrow f( \overline{z}) =u(x,y) - iv(x,y)[/tex]

- #7

- 133

- 4

Anyway suppose you write z = x+ iy then the conjugate is x - iy

so take u(x,y) to u(x,-y) and v(x,y) to v(x,-y). Then (and of course taking the conjuagte of the function also means another minus sign. The the Cauchy Riemann relation will provide the answer.

- #8

- 133

- 4

[itex] f(z) = f(x,y) = u(x,y) + iv(x,y) \rightarrow f( \overline{z}) =u(x,y) - iv(x,y)[/itex]

This is exactly what needs proving. Where you use the fact that the function is entire.

- #9

- 158

- 0

Then [itex]\overline{f(\bar{z})} = u(x,-y)-iv(x,-y)[/itex]??

- #10

I like Serena

Homework Helper

- 6,579

- 176

Then [itex]\overline{f(\bar{z})} = u(x,-y)-iv(x,-y)[/itex]??

Yes.

- #11

- 158

- 0

Yes.

Since f is holomorphic, we know:

[tex]u_x = v_y \ \text{and} \ u_y = -v_x[/tex]

Now, how do I use [itex]F(z)=\overline{f(\bar{z})}=u(x,-y)-iv(x,-y)[/itex].

I read that I need to use C.R. equations. I need to show:

[tex]u_x(x,-y) = v_y(x,-y) \ \text{and} \ -u_y(x,-y) = v_x(x,-y)[/tex]

Now, what should I do or how should I approach it?

- #12

I like Serena

Homework Helper

- 6,579

- 176

So I assume you're supposed to show that F(z) is holomorphic?

If so, according to C.R. you should check that ##\Re(F_x)=\Im(F_y)## and that ##\Re(F_y)=-\Im(F_x)##, starting from the fact that f(z) is holomorphic...

- #13

- 158

- 0

So I assume you're supposed to show that F(z) is holomorphic?

If so, according to C.R. you should check that ##\Re(F_x)=\Im(F_y)## and that ##\Re(F_y)=-\Im(F_x)##, starting from the fact that f(z) is holomorphic...

How do I check that?

I wrote that in terms of u and v in the post just above yours.

- #14

I like Serena

Homework Helper

- 6,579

- 176

How do I check that?

I wrote that in terms of u and v in the post just above yours.

Well, if ##u_x(x,y)=v_y(x,y)## for all x and y, don't you also have ##u_x(x,-y)=v_y(x,-y)##?

- #15

- 158

- 0

Well, if ##u_x(x,y)=v_y(x,y)## for all x and y, don't you also have ##u_x(x,-y)=v_y(x,-y)##?

I need to prove the second part. So can I say [itex]y=-y[/itex]

- #16

I like Serena

Homework Helper

- 6,579

- 176

I need to prove the second part. So can I say [itex]y=-y[/itex]

Hmm, no you can't say y=-y.

But since ##u_x(x,y)=v_y(x,y)## is true for all x and y, you could also say ##u_x(x,w)=v_y(x,w)## is true for all x and w.

Now define y=-w...

- #17

- 158

- 0

Hmm, no you can't say y=-y.

But since ##u_x(x,y)=v_y(x,y)## is true for all x and y, you could also say ##u_x(x,w)=v_y(x,w)## is true for all x and w.

Now define y=-w...

I am not sure what you are attempting to allude to from the ellipses.

- #18

I like Serena

Homework Helper

- 6,579

- 176

In particular, if we define y=-w, that means that ##u_x(x,-y)=v_y(x,-y)## is true for all x and y.

Put otherwise, the relation holds true for any point in the complex plane.

It does not matter if we put a minus sign in front of the imaginary part of a point, as long as we do so consistently.

The resulting points (x,-y) are all in the same complex plane for which the relation holds true.

- #19

- 158

- 0

In particular, if we define y=-w, that means that ##u_x(x,-y)=v_y(x,-y)## is true for all x and y.

Put otherwise, the relation holds true for any point in the complex plane.

It does not matter if we put a minus sign in front of the imaginary part of a point, as long as we do so consistently.

The resulting points (x,-y) are all in the same complex plane for which the relation holds true.

Thanks. Sorry for not being able to decipher that myself.

Share: